Academic writing skills - Peter Chin (Cambridge University Press, 2012)
A three-volume essay writing course for students in American English. Academic Writing Skills 1 takes students through a step-by-step process from writing a paragraph to essays. It is appropriate for students new to academic writing who need general training in essay writing skills